Cromatografia em contra-corrente de gotejamento na separação de substâncias fenólicas de Neuropogon aurantiaco-ater - Pozzebon, J. M. [UNESP]; Vilegas, Wagner [UNESP]; Honda, N. K. [UNESP] (My University, 2001)
This work reports the separation of phenolic compounds present in the metabolic extract of the lichen Neuropogon aurantiaco-ater (Usniaceae). The crude extract was fractionated by droplet counter-current chromatography using a solvent mixture of high polarity (chloroform:methanol:water at 43:37:20, in ascending mode). The separation resulted in the isolation of usnic and protocetratic acid, which were identified by TLC, HPLC, and NMR tests.
Droplet counter-current chromatography in the separation of phenolic substances from Neuropogon aurantiaco-ater
Keywords: Chromatography; Countercurrent distribution; Lichens; Phenols; chloroform; methanol; natural product; phenol derivative; protocetratic acid; unclassified drug; usnic acid; water; counter current chromatography; extraction; fractionation; high performance liquid chromatography; lichens; Neuropogon aurantiaco ater; nonhuman; nuclear magnetic resonance; thin layer chromatography